Iron Intake and Hemoglobin Levels in Stunting in Adolescent - Puristasari, Addistyane; Fatimah, Siti Nur; Faisal, Faisal (Althea Medical Journal, 2016)
Background: Growth problem, such as stunting is still a major issue in the world. The prevalence ofÂ stunting in Indonesia increases throughout the years. Chronic undernutrition in adolescent with stunting,Â low socioeconomic, and education levels in a family can contribute to low iron intake. Low iron intake leadsÂ to low hemoglobin level. This study aimed to compare iron intake and hemoglobin level between stuntingÂ and non-stunting adolescent.Methods: This study was conducted to 59 respondents aged 11â14 years old from a Junior High School inÂ Jatinangor, West Java from September to October 2014. Those respondents were divided into two groups:Â stunting and non-stunting group. This study was an analytic comparative study using cross-sectional method.Â Data were collected through body height measurement, hemoglobin level examination, and interviews ofÂ iron-containing food intake. The collected data were analyzed using t-test and Mann-Whitney U test.Results: Twenty eight of 59 subjects were stunting and 31 were normal. The mean of hemoglobin level wasÂ 12.95 (0.95) in stunting adolescent and 13.66 (1.35) in non-stunting adolescent. The mean iron intake wasÂ 23.9 (24.39) mg/day in stunting adolescent and 23 (22.6) mg/day in non-stunting adolescent. There was aÂ difference of hemoglobin between those groups, but not in iron intake.Conclusions: Stunting adolescent has lower hemoglobin levels compared to non-stunting adolescent. ThereÂ is no difference of iron intake levels between stunting and non-stunting adolescent. [AMJ.2016;3(2):175â80]DOI:Â 10.15850/amj.v3n2.782